Acetoacetate, a ketone body, attenuates neuronal bursts in acutely-induced epileptiform slices of the mouse hippocampus - Wen, Hao; Sada, Nagisa; Inoue, Tsuyoshi (Frontiers in Cellular Neuroscience, 2025)
The ketogenic diet increases ketone bodies (β-hydroxybutyrate and acetoacetate) in the brain, and ameliorates epileptic seizures in vivo. However, ketone bodies exert weak or no effects on electrical activity in rodent hippocampal slices. Especially, it remains unclear what kinds of conditions are required to strengthen the actions of ketone bodies in hippocampal slices. In the present study, we examined the effects of acetoacetate on hippocampal pyramidal cells in normal slices and epileptiform slices of mice. By using patch-clamp recordings from CA1 pyramidal cells, we first confirmed that acetoacetate did not change the membrane potentials and intrinsic properties of pyramidal cells in normal slices. However, we found that acetoacetate weakened spontaneous epileptiform bursts in pyramidal cells of epileptiform slices, which were acutely induced by applying convulsants to normal slices. Interestingly, acetoacetate did not change the frequency of the epileptiform bursts, but attenuated individual epileptiform bursts. We finally examined the effects of acetoacetate on excitatory synaptic barrages during epileptiform activity, and found that acetoacetate weakened epileptiform bursts by reducing synchronous synaptic inputs. These results show that acetoacetate attenuated neuronal bursts in epileptiform slices, but did not affect neuronal activity in normal slices, which leads to seizure-selective actions of ketone bodies.